Decoding Parkinson's disease – iPSC-derived models in the OMICs era - Krach, Florian; Bogiongko, Marios Evangelos; Winner, Beate (Molecular and Cellular Neuroscience, 2020)
Parkinson's disease (PD) is a neurodegenerative disorder characterized by the loss of dopaminergic neurons in the midbrain. In recent years, researchers have started studying PD using induced pluripotent stem cell (iPSC) models of the disease. Surprisingly, few studies have combined iPSC-technology with the so-called powerful ‘omics’ approaches. Here, we review the current state of omics applications used in combination with iPSC-derived models to study PD. Our focus is on studies investigating transcriptional changes and publications using proteomics applications. Lastly, we discuss current caveats in the field and identify potential future directions to obtain novel insights into PD pathology.
CRIS-Team Scopus Importer:2020-06-02
Keywords: Disease modeling; iPSC; Parkinson's disease; Proteomics; RNA-seq; Transcriptomics